Sexualization in the coping process of HIV-infected gay men - Sandfort, Theo; Clement, Ulrich; Knobel, J.; Keet, R.; de Vroome, E. M. M. (Clinical psychology & psychotherapy, 1995)
This study explores determinants of unsafe sex, specifically in HIV-infected gay men. It is assumed that safe sex in HIV-positive men is determined by other factors than in men with an unknown or negative serostatus. For HIV-positive men it is much less an issue of protecting oneself, and more so an issue of protecting the other. It is hypothesized that for HIV-positive men, practising safe and unsafe sex is the outcome of a coping process, in which the stress of being infected is mediated by several factors, potentially resulting in a tendency to compulsive sexual behaviour (sexualization). A path analytic test supports the theoretical model. However, sexualization, especially the tendency to have sex to make oneself feel better, is only related to the number of sex partners one has had and not to having practised unsafe sex. This may imply that practising safe and unsafe sex should be much more understood from an interpersonal than an intrapersonal perspective.